Land application of mine water causes minimal uranium loss offsite in the wet-dry tropics: Ranger Uranium Mine, Northern Territory, Australia. (November 2015) - Mumtaz, Saqib; Streten, Claire; Parry, David L.; McGuinness, Keith A.; Lu, Ping; Gibb, Karen S.
Abstract: Ranger Uranium Mine (RUM) is situated in the wet-dry tropics of Northern Australia. Land application (irrigation) of stockpile (ore and waste) runoff water to natural woodland on the mine lease is a key part of water management at the mine. Consequently, the soil in these Land Application Areas (LAAs) presents a range of uranium (U) and other metals concentrations. Knowledge of seasonal and temporal changes in soil U and physicochemical parameters at RUM LAAs is important to develop suitable management and rehabilitation strategies. Therefore, soil samples were collected from low, medium, high and very high U sites at RUM LAAs for two consecutive years and the effect of time and season on soil physicochemical parameters particularly U and other major solutes applied in irrigation water was measured. Concentrations of some of the solutes applied in the irrigation water such as sulphur (S), iron (Fe) and calcium (Ca) showed significant seasonal and temporal changes. Soil S, Fe and Ca concentration decreased from year 1 to year 2 and from dry to wet seasons during both years. Soil U followed the same pattern except that we recorded an increase in soil U concentrations at most of the RUM LAAs after year 2 wet season compared to year 2 dry season. Thus, these sites did not show a considerable decrease in soil U concentration from year 1 to year 2. Sites which contained elevated U after wet season 2 also had higher moisture content which suggests that pooling of U containing rainwater at these sites may be responsible for elevated U. Thus, U may be redistributed within RUM LAAs due to surface water movement. The study also suggested that a decrease in U concentrations in LAA soils at very high U (>900 mg kg −1 ) sites is most likely due to transport of particulate matter bound U by surface runoff and U may not be lost from the surface soil due to vertical movement through the soil profile. Uranium attached to particulate matter may reduce its potential for environmental impact. These findings suggest that U is effectively adsorbed by the soils and thus land application may serve as a useful tool for U management in the wet-dry tropics of northern Australia. Highlights: Uranium is bound to soil particles at Ranger Uranium Mine Land Application Areas. Uranium bound to soil particles is displaced by surface runoff water. Uranium is not leached down the soil profile at Land Application Areas. Soil sulphur, iron and calcium concentrations showed significant seasonal and temporal changes.